Assessing the Influence of Muzaraah Agreements on Farmers' Well-being in Kujon Village - Hakim, Lukmanul; Handoko, Rian; Munir, Mukhlis Sirotul (Universitas Mercu Buana, 2022)
The purpose of this study was to determine how the implementation and influence of the muzaraah contract on the welfare of farmers in Kujon village, Ceper district, Klaten district. This research uses field research and is qualitative in nature. Data obtained from interviews and documentation as well as data analysis using inductive thinking and answers from sources. This study also aims to determine the effect of the muzara'ah contract applied by farmers in Kujon village, Ceper sub-district, Klaten district on their welfare using the prosperous family indicator by the BKKBN and see its conformity with the muzara'ah contract theory. The results of this study concluded that the implementation of the muzaraah contract carried out by both parties was carried out verbally, then both parties also discussed profit sharing. The profit sharing applied by both parties is still adjusted to the custom that has been applied in Kujon village where the amount of profit sharing applied is 1/3:2/3. The muzaraah contract for the community in Kujon village is very influential on the welfare of sharecroppers where previously they could only meet basic needs, but now from the 7 farmers studied, all of them show an increase in their welfare.